Catechols: a new class of carbonic anhydrase inhibitors. Issue 85 (1st October 2020) - D'Ambrosio, Katia; Carradori, Simone; Cesa, Stefania; Angeli, Andrea; Monti, Simona M.; Supuran, Claudiu T.; De Simone, Giuseppina
Abstract : Catechols adopt a peculiar binding mode to the CA active site which involves both the zinc bound water molecule and the "deep water". Abstract : To date, catechols have been only poorly investigated as carbonic anhydrase (CA) inhibitors. Here we report the first structural information on the CA inhibition mechanism of these molecules, showing that they adopt a peculiar binding mode to the enzyme active site which involves the zinc-bound water molecule and the "deep water".